1998
DOI: 10.1042/bj3310089
|View full text |Cite
|
Sign up to set email alerts
|

3,5,3′-Tri-iodo-l-thyronine acutely regulates a protein kinase C-sensitive, Ca2+-independent, branch of the hepatic α1-adrenoreceptor signalling pathway

Abstract: This work aimed to investigate the acute effect of the thyroid hormone 3,5,3'-tri-iodo-L-thyronine (T3) in regulating the hepatic metabolism either directly or by controlling the responsiveness to Ca2+-mobilizing agonists. We did not detect any acute metabolic effect of T3 either in perfused liver or in isolated liver cells. However, T3 exerted a powerful inhibitory effect on the alpha1-adrenoreceptor-mediated responses. The promptness of this T3 effect rules out that it was the result of rate changes in gene(… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

1999
1999
2009
2009

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 51 publications
0
3
0
Order By: Relevance
“…Ion fluxes are common consequences of the rapid workings of steroidal compounds. The channel opening most commonly affected (or more frequently measured) is Ca++ (24,26,52,55,57,59,60,(76)(77)(78)(79)(80)(81)(82)(83)(84)(85)(86)(87)(88)(89)(90)(91)(92)(93)(94)(95). These examples include the actions of glucocorticoids (95), progestins (24,26,(76)(77)(78)(79)(80), vitamin D (52, 81, 91), thyroid hormone (94), androgens (81,82,90), mineralocorticoids (55), and estrogens (59,60,(83)(84)(85)(86)(87)(88)(89)93).…”
Section: Cellular Mechanisms Associated With Membrane-initiated Steroid Actionsmentioning
confidence: 99%
See 1 more Smart Citation
“…Ion fluxes are common consequences of the rapid workings of steroidal compounds. The channel opening most commonly affected (or more frequently measured) is Ca++ (24,26,52,55,57,59,60,(76)(77)(78)(79)(80)(81)(82)(83)(84)(85)(86)(87)(88)(89)(90)(91)(92)(93)(94)(95). These examples include the actions of glucocorticoids (95), progestins (24,26,(76)(77)(78)(79)(80), vitamin D (52, 81, 91), thyroid hormone (94), androgens (81,82,90), mineralocorticoids (55), and estrogens (59,60,(83)(84)(85)(86)(87)(88)(89)93).…”
Section: Cellular Mechanisms Associated With Membrane-initiated Steroid Actionsmentioning
confidence: 99%
“…Kinases are also frequently controlled by their own phosphorylation status. Examples of rapid steroid-induced changes in kinase activities include many different categories of protein kinases including both tyrosine and serinekhreonine kinases (29, 12 l), cyclic nucleotide-, Ca++-, inositol phosphate-, or DAG-dependent kinases (24,35,41,54,76,94,101,113,118,(122)(123)(124), and kinases associated with cell proliferation such as MAP kinase (19,30,123,(125)(126)(127)(128) and other ERKs (19,29,30,62,128,129). One wonders if further analysis will also reveal participation of phosphatase activities in these schemes, although no examples of this part of the general mechanism have yet appeared.…”
Section: Cellular Mechanisms Associated With Membrane-initiated Steroid Actionsmentioning
confidence: 99%
“…Together, these results provide evidence for the involvement of plasma membrane receptors and plasma membrane-associated signal transduction pathways in the short-term nongenomic effects of thyroid hormones. The short-term effects of thyroid hormones were in many cases found to involve signal transduction pathways and second messenger systems that lead to activation of protein kinases (5,20,28,35,36,41,46,47,62). It was recently shown that in CV-1 cells, rapid effects elicited by T 4 were initiated at the plasma membrane level through the interaction with an ␣ V ␤ 3 integrin (5).…”
mentioning
confidence: 99%